2018
DOI: 10.1111/plb.12883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous versus pulsed drought stress on physiology and growth of wheat

Abstract: In the course of climate change, crop plants are exposed to both altered precipitation volumes and frequencies in many cultivation areas. Reduced water availability and longer periods without precipitation can lead to changes in plant physiology and productivity. In this greenhouse study, we investigated physiological responses, including maximum quantum yield of photosystem II (F /F ) and water use efficiency (WUE) as well as diverse productivity-related parameters, including grain yield per plant, to continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…This finding could be due to higher evaporation from soil after pulse irrigation and/or differences in root systems between cd and pd plants. In a previous experiment in which wheat plants of the same cultivar were differently irrigated and harvested after fruit ripening, the WUE apl based on the grain yield, but not that based on the vegetative biomass, was higher in cd than in pd plants 47 . Both studies highlight that the investment of wheat plants into vegetative and generative growth under drought depends on the irrigation frequency and the improvement of the WUE apl and that the harvest index is limited at low irrigation frequencies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding could be due to higher evaporation from soil after pulse irrigation and/or differences in root systems between cd and pd plants. In a previous experiment in which wheat plants of the same cultivar were differently irrigated and harvested after fruit ripening, the WUE apl based on the grain yield, but not that based on the vegetative biomass, was higher in cd than in pd plants 47 . Both studies highlight that the investment of wheat plants into vegetative and generative growth under drought depends on the irrigation frequency and the improvement of the WUE apl and that the harvest index is limited at low irrigation frequencies.…”
Section: Discussionmentioning
confidence: 66%
“…Six days after sowing, five seedlings were planted together in an equal distance of 6 cm surrounding a central seedling in each of 60 pots (4 L, 15.7 × 15.7 × 23.3 cm; Meyer, Rellingen, Germany) to simulate natural competition. Each pot contained 4,185 g of the substrate mentioned above, with a substrate water content of 23% (determined gravimetrically in a previous experiment 47 ). Pots had holes at the bases to allow draining and were placed on dishes to prevent water loss after leaching.…”
Section: Methodsmentioning
confidence: 99%
“… Tanner and Sinclair (1983) proposed that VPD is equal to 0.75 of the difference between maximum daily vapor pressure and minimum daily vapor pressure. Abbate et al (2004) subsequently concluded that the weighting coefficient in the calculation of VPD for Argentine environments was 0.72.…”
Section: A Mechanistic Viewmentioning
confidence: 99%
“…The physiological changes of wheat plants under drought stress, and the molecular mechanisms underpinning the response to drought stress have been well studied [6,7,8,9]. Relative water content (RWC), relative conductivity, malonaldehyde (MDA), and proline content are important physiological indicators that reflect plant drought tolerance.…”
Section: Introductionmentioning
confidence: 99%